Patterns of chemotherapy use with primary radiotherapy for localized bladder cancer in patients 65 or older - Ghali, Fady; Holt, Sarah K.; Koehne, Elizabeth L.; Chen, Jonathan J.; Weg, Emily S.; Liao, Jay J.; Zeng, Jing; Grivas, Petros; Hawley, Jessica E.; Hsieh, Andrew C.; Montgomery, Robert Bruce; Wright, Jonathan L. (Frontiers in Oncology, 2024)
Introduction Bladder preservation with concurrent chemoradiotherapy after maximum transurethral resection of bladder tumor is an alternative to radical cystectomy in select patients with muscle invasive bladder cancer (MIBC). Concurrent administration of radio-sensitizing chemotherapy and radiation therapy (RT) has been shown to have superior disease control compared with RT alone and can often be administered with modest added toxicity. We sought to describe national patterns of chemotherapy use. Methods The linked surveillance, epidemiology, and end results (SEER)-Medicare database was used to identify patients with cT2-4, N0/X, M0/X BC who received radiation between 2004 and 2018. Data on demographics, clinicopathologic factors, therapy and outcomes were extracted. Concurrent utilization of chemotherapy with RT was also identified (CRT). Multivariate logistic regression (MVA) models were used to explore factors associated with receipt of chemotherapy and overall survival (OS). Results 2190 patients met inclusion criteria. Of these, 850 (38.8%) received no chemotherapy. Among those receiving chemotherapy, the most frequent regimens were single agent carboplatin, cisplatin, or gemcitabine. Factors that were independently associated with decreased likelihood of chemotherapy use were increasing age (OR 0.93, CI 0.92 – 0.95), Hispanic race (compared with White, OR 0.62, CI 0.39 – 0.99), cT3 or T4 (compared with cT2, OR 0.70, CI 0.55 – 0.90), and lower National Cancer Institute comorbidity index (OR 0.60, CI 0.51 – 0.70) (p < 0.05). Variables independently associated with increased likelihood of receipt of chemotherapy were married status (OR 1.28, CI 1.06 – 1.54), higher socioeconomic status (OR 1.31, CI 1.06 – 1.64), and later year of diagnosis (OR 1.09, CI 1.06 – 1.12). Receipt of concurrent chemotherapy with RT was associated with superior OS compared with RT alone. Conclusion Over a third of patients >/65 years old receiving curative-intent RT for MIBC do not receive concurrent chemotherapy. Considering the improvement in oncologic outcomes with CRT over RT alone and more options, such as low dose gemcitabine which can be administered with modest toxicity, efforts are needed to identify barriers to utilization and increase the use of radio-sensitizing chemotherapy.